Three-Component Efficient Synthesis of 2-Amino-3-cyano-4H-pyrans Catalyzed by Diammonium Hydrogen Phosphate in Aqueous Media - Taghva, Pardis H.; Kabirifard, Hassan (Current Organocatalysis, 2021)
Background: The present method is facile, green and effective for the synthesis of 2- amino-3-cyano-4H-pyran derivatives which are obtained by one-pot three-component condensation reactions of aromatic aldehydes, malononitrile and methyl acetoacetate using diammonium hydrogen phosphate (DAHP) in aqueous ethanol at room temperature. Methods: 2-Amino-3-cyano-4H-pyrans were synthesized through a one-pot three-component tandem Knoevenagel cyclocondensation reaction of aromatic aldehydes, malononitrile, and methyl acetoacetate in the presence of 10 mol% of DAHP as a catalyst under aqueous ethanol medium at room temperature. All obtained structures were confirmed by their physical constant, IR, 1H NMR, 13C NMR spectroscopy, and also elemental analyses for new derivatives. Results: Three-component synthesis of 2-amino-3-cyano-4H-pyrans catalyzed by DAHP with aromatic aldehydes, malononitrile and methyl acetoacetate in aqueous ethanol medium at room temperature was prepared. The achieved derivatives (nine entries) were well synthesized in excellent yields. Conclusion: The present method is straightforward, quick, and most efficient green protocol for the synthesis of 2-amino-3-cyano-4H-pyran derivatives using highly inexpensive, easily handle and, nontoxic DAHP as an efficient catalyst in aqueous ethanol medium at room temperature.
Keywords: malononitrile